PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI SUPLAI DAYA POMPA AIR SUBMERSIBLE INOTO 2 HP DI DUSUN LERAN - Azis Bukhori, Ogik; Setiawan, I Nyoman; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p14, 2022)
The Water Pump System in Leran Hamlet is intended to meet the water needs of the community, the pump used is an INOTO 2 HP submersible water pump driven by a 1 phase electric motor. This study designing grid-tied solar system based on the water pump power which has simulated with PVSyst. In this study, the water pump is projected to lift water from the ground with a volume of 1,328 m/month according to customer water usage. The Solar Power Plant system uses 10 unit of 335 Wp Risen RSM72-6-335P solar modules and an 4 kW inverter Solis 1P4K-4G. The simulation results show that the annual energy production of PLTS is 4.194 MWh/year with solar fraction 1.28 which means Solar Power Plant is able to meet the energy needs of water pump. The investment analysis resulted in Net Present Value is Rp.145,867,228, Profitability Index is 3.6 and Discounted Payback Period is 4.3 years which indicates that the investment is feasible.